Abnormal ranges of vital signs in children in Japanese prehospital settings. Issue 4 (14th July 2015) - Nosaka, Nobuyuki; Muguruma, Takashi; Knaup, Emily; Tsukahara, Kohei; Enomoto, Yuki; Kaku, Noriyuki
Abstract : Aim: The revised Fire Service Law obliges each prefectural government in Japan to establish a prehospital acuity scale. The Foundation for Ambulance Service Development (FASD) created an acuity scale for use as a reference. Our preliminary survey revealed that 32 of 47 prefectures directly applied the FASD scale for children. This scale shows abnormal ranges of heart rate and respiratory rate in young children. This study aimed to evaluate the validity of the abnormal ranges on the FASD scale to assess its overall performance for triage purposes in paediatric patients. Methods: We evaluated the validity of the ranges by comparing published centile charts for these vital signs with records of 1, 296 ambulance patients. Results: A large portion of the abnormal ranges on the scale substantially overlapped with the normal centile charts. Triage decisions using the FASD scale of vital signs properly classified 22% ( n  = 287) of children. The sensitivity and specificity for high urgency were as high as 91% (95% confidence interval, 82–96%) and as low as 18% (95% confidence interval, 16–20%). Conclusion: We found there is room for improvement of the abnormal ranges on the FASD scale.